Pancasila dan Sistem Peradilan Pidana: Analisis terhadap Prinsip Keadilan dalam Penanganan Kasus Korupsi - Ashfiya Nur Atqiya; Ahmad Muhamad Musain Nasoha; Rory Haniffiyyah Riz; Annisa Fitri Oktaviani; Annisaa Nur Khalimah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research explores the application of Pancasila principles of justice in the Indonesian criminal justice system, especially in the handling of corruption cases. Pancasila as the foundation of the state contains moral and ethical values that should guide law enforcement. However, its application is often constrained by political influence and corruption within judicial institutions. This study uses a qualitative approach with case studies and comparative analysis, involving literature review, expert interviews, and analysis of corruption cases in Indonesia. The findings show that while the principles of Pancasila provide a strong foundation of justice, implementation is less effective due to external influences. Judicial reform, increased transparency, and protection for corruption whistleblowers are recommended to strengthen the implementation of the Pancasila principles and their conformity with international standards.